Implementation of Blue Economy Policy in Marine Resource Management to Support Economic Growth - Imsar; Purnama Ramadani Silalahi; Nurul Aulia Dewi; Dimas Surya (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Background: Aceh Province has abundant marine resources with a coastline exceeding 2,500 kilometers, yet the fisheries sector's contribution to Gross Regional Domestic Product remains low at only 5.23%. Excessive exploitation, marine pollution, and mangrove degradation threaten ecological sustainability and coastal community welfare. The blue economy concept offers a sustainable development approach balancing economic growth and environmental preservation. Research Gap: Previous studies have generally focused on specific sectors such as coral reef conservation without integrating multidisciplinary analysis encompassing ecological, socio-cultural, and institutional policy aspects comprehensively. Limited research has examined blue economy implementation in Aceh with a focus on local wisdom integration. Novelty: This study offers an integrative approach combining economic, ecological, and institutional governance dimensions within a single analytical framework. It specifically examines the role of Panglima Laot traditional institutions in marine governance, an aspect underexplored in previous literature, and proposes an adaptive policy model integrating ecologically based incentives. Method: A qualitative descriptive analytical approach was employed. Data were collected through in-depth interviews, field observations, and documentation with informants including traditional leaders (Panglima Laot) and representatives of the Maritime Affairs and Fisheries Agency. Data analysis followed the Miles and Huberman interactive model through data reduction, presentation, and conclusion drawing. Results: Implementation of the blue economy in Aceh includes marine ecosystem conservation, mangrove rehabilitation (100 hectares annually), fish house construction, and establishment of 149,000 hectares of Marine Protected Areas. Challenges include limited human resources, inadequate infrastructure, budget constraints, and overlapping authority between central and regional governments. Panglima Laot traditional institutions play a strategic role in regulating fishing zones, enforcing customary bans, and strengthening participatory marine governance. Conclusion: Integration of blue economy policies with local wisdom is essential for realizing sustainable and equitable marine resource management. Strengthening customary institutions, improving inter-agency coordination, and enhancing fisher capacity are critical for optimizing marine potential and improving coastal community welfare.